2017
DOI: 10.1111/jfr3.12325
|View full text |Cite
|
Sign up to set email alerts
|

Explaining stability and change. Comparing flood risk governance in Belgium, France, the Netherlands, and Poland

Abstract: The closing article of this special issue provides a comparative analysis of flood risk governance (FRG) in four European countries and tries to explain why FRG in the Netherlands and Poland is more stable than in Belgium and France. It examines the role of mechanisms of path dependency and path change. Inspired by the conceptual framework developed in the introductory article, this article provides an overview of dynamics in FRG in the four countries and identifies major trends and tendencies. It discusses fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…For the six countries studied in detail, the authors found national approaches to flood risks and their governance to be marked by a dominance of public actors (especially in the Netherlands, Poland, France, and Belgium) as well as central authorities with strong legal powers (especially in Poland and France). Similarly, Liefferink et al [17] reported on the strong and powerful role of expertise and expert bodies (especially in the Netherland and Poland), an observation confirmed by other authors, like Lange and Garrelts [18] for Germany, or Mostert et al [19] and Bergsma [20] for the Netherlands.…”
Section: State Of the Research And Own Conceptual Frameworkmentioning
confidence: 58%
See 1 more Smart Citation
“…For the six countries studied in detail, the authors found national approaches to flood risks and their governance to be marked by a dominance of public actors (especially in the Netherlands, Poland, France, and Belgium) as well as central authorities with strong legal powers (especially in Poland and France). Similarly, Liefferink et al [17] reported on the strong and powerful role of expertise and expert bodies (especially in the Netherland and Poland), an observation confirmed by other authors, like Lange and Garrelts [18] for Germany, or Mostert et al [19] and Bergsma [20] for the Netherlands.…”
Section: State Of the Research And Own Conceptual Frameworkmentioning
confidence: 58%
“…A more comprehensive assessment of flood risk governance arrangements (FRGAs) was provided by the STAR-FLOOD project: The project was comparative in scope, analyzing and contrasting FRGAs in six European countries. It went beyond the EU Floods Directive and its national implementation by taking a more long-term perspective, analyzing FRGA dynamics from the 1970s up to the present, thus, trying to explain stability and change in the sector [17]. In addition to that, similar to our paper, STAR-FLOOD engaged in the question of whether and how climate change might have an impact on FRGAs.…”
Section: State Of the Research And Own Conceptual Frameworkmentioning
confidence: 97%
“…et al, 2011, p. 174). This asks more of regional and local authorities in their spatial planning, although regulatory changes are slow (Liefferink, Wiering, Crabbé, & Hegger, 2018). In the specific cases studied here, both municipalities experienced major riverine floods (the Meuse River) during the 1990s, raising questions about their policy responses, and the extent of collective learning in policymaking in coming to terms with the evolving national institutional context.…”
Section: Collective Learning In Subnational Flood Risk Policymakingmentioning
confidence: 99%
“…This process strives to influence policy (for example, by establishment of watershed jurisdictions) as well as practice (evidence-based decision making using cost cost-benefit analysis, collaborative management by public participation, enhancing ecological status by win-win measures in the light of Water Directive and more). These days, a substantial body of research is dedicated to comparative analysis of EU-countries, their respective FR governance setting and resulting policies and policy tools in the view of legal, planning, economics and participatory aspects (Raška 2015;Hegger et al 2016b;Liefferink et al 2018). On the contrary, little if any research is undertaken regarding the actual effectiveness of the watershed (catchment) during floods in of the watershed (catchment) FR management plans (the fruits of the governance and policy tools)-most probably because 11 years are not a sufficient time span for determinations of this kind.…”
mentioning
confidence: 99%
“…First things first-who is in charge? Studies in some EU countries show that, while the central state remained the core actor in flood risk governance, the decentralization process transferred significant responsibilities to the municipalities (Wiering et al 2018;Liefferink et al 2018). In other EU countries, such as Ireland, the National Office of Public Works (OPW) is the jurisdiction to map the risks and to run the FRM plans.…”
mentioning
confidence: 99%